Spectroscopic and time-resolved fluorescence emission properties of a cationic and an anionic porphyrin in biomimetic media and Candida albicans cells - Novaira, Mercedes (2012)
Spectroscopic and time-resolved fluorescence emission techniques were used to provide information for the interaction of 5,10,15,20-tetrakis(4-N,N,N- trimethylammoniumphenyl) porphyrin (TMAP 4+) and 5,10,15,20- tetrakis(4-sulphonatophenyl) porphyrin (TPPS 4-) with different biomimetic media and with Candida albicans cells. In n-heptane/sodium bis(2-ethylhexyl)sulfosuccinate (AOT)/water and benzene/benzyl-n- hexadecyldimethylammonium chloride (BHDC)/water reverse micelles interactions were dependent on the micellar interface and the amount of water dispersed in the microemulsion. It was also observed that the DNA binding of cationic porphyrin TMAP 4+ led to two lifetimes. In vitro investigations showed that TMAP 4+ is bound to C. albicans. Fluorescence lifetime measurements and fluorescence microscopic images provided additional insight into the effects of porphyrin uptake by cells. The results reveal a double localization of TMAP 4+ inside of C. albicans cells. Thus, a redistribution of TMAP 4+ was observed in unwashed cells, probably due to a relocalisation of molecules that were weakly bound to the cells or remained in solution. However, this effect was not found with molecules tightly bound in the cells, after one washing step.